1998
DOI: 10.1099/00221287-144-5-1189
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in the Mycobacterium tuberculosis complex based on variable numbers of tandem DNA repeats

Abstract: Genetic loci containing variable numbers of tandem repeats (VNTR loci) form the basis for human gene mapping and identification, forensic analysis and paternity testing. The variability of bacterial tandem repeats has not been systematically studied. Eleven tandem repeat loci in the M. tuberculosis genome were analysed. Five major polymorphic tandem repeat (MPTR) loci contained 15-bp repeats with substantial sequence variation in adjacent copies. Six exact tandem repeat (ETR) loci contained large DNA repeats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
466
2
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(478 citation statements)
references
References 25 publications
5
466
2
5
Order By: Relevance
“…The M. bovis strains were also analysed by mycobacterial interspersed repetitive units (MIRU) -variable-number tandem repeats (VNTR) aimed at loci ETR-A [10] and loci 4 [36].…”
Section: Molecular Characterisation Of M Bovis Isolatesmentioning
confidence: 99%
“…The M. bovis strains were also analysed by mycobacterial interspersed repetitive units (MIRU) -variable-number tandem repeats (VNTR) aimed at loci ETR-A [10] and loci 4 [36].…”
Section: Molecular Characterisation Of M Bovis Isolatesmentioning
confidence: 99%
“…This allowed allocation of each isolate to one of the small number of readily identifiable M. bovis clones that occur in Britain (Smith et al, 2003); exploratory analysis revealed that an alternative typing method (using variable number tandem repeats; Frothingham and Meeker-O'Connell, 1998) provided no additional information.…”
Section: Diagnosis and Severity Of M Bovis Infection In Badgersmentioning
confidence: 99%
“…Thirty-five polymorphic tandem repeat (TR) loci, ranging in size between 50 and 111 base pairs (bp), were reported to have potential value. 5,15,16,19 After preliminary testing, 3 loci (0580, 3006, 3191) were dropped from consideration because the primers for these loci amplified the same TR locus as other primers (0580S, 3007, 3192, respectively), and 5 loci (4156, 2074, 1612, 2059, 3155) were dropped because of multiple banding patterns or no amplification of product. These problems were not resolved by adjusting polymerase chain reaction (PCR) conditions or cycling parameters.…”
Section: Tandem Repeat Locimentioning
confidence: 99%